Transfert De Compétences Et De Ressources Dans Le Secteur De L’eau Potable Dans La Commune De Ouinhi Au Sud-Est Du Bénin - Jérôme, Orounla Kotchikpa (European Scientific Journal, ESJ, 2018)
Following the council and municipal elections of 2003 in Benin, the government engaged on a decentralization policy. In the drinking water sector, the reform has enhanced the redefining of the roles and responsibilities of different agents and institutions. Based on this observation, a qualitative study has been undertaken to analyze and describe the new process of public drinking water supply. This research collected data from sixty respondents. It involved the use of investigative techniques such as documentation, participant observation and interviewing. According to the study, certain skills and resources had been transferred and are administered by the council of Ouinhi, as well as the other councils of Benin. However, the resources are not often delivered on time. As a result, the municipality is faced with several financial, technical, organizational and material drawbacks.